CHANGE OF THE NUMBER AND SOCIO-DEMOGRAPHIC CHARACTERISTICS OF THE EPISCOPAL DIOCESES OF THE RUSSIAN ORTHODOX CHURCH IN THE SOUTH OF WESTERN SIBERIA AT THE BEGINNING OF THE XXI CENTURY - V. A. Ovchinnikov (Вестник Кемеровского государственного университета, 2017)
The article is based on the comparative analysis of regulatory and administrative documents, record keeping and information and reference materials, periodicals and Internet resources. The author identifies the causes, determines the performance, features and results of the process of changing the size and characteristics of the Episcopal body of Russian Orthodox Church dioceses in the south of Western Siberia at the beginning of the XXI century. The process in question was directly related to the reform of "splitting" the dioceses of the Russian Orthodox Church in 2011 – 2015. It proceeded in line with national trends, but had a number of negative consequences for the dioceses of the region due to the fact that they being "young" had a less developed organizational and management structure, material and economic basis compared with the dioceses of the European part of Russia. The reform, which has a positive deferred effect on the ROC, at the target stage, led to an increase in the number of dioceses and ruling bishops from 5 to 18, to the rejuvenation of the Episcopal body while reducing the level of theological education, management experience and monastic life. Based on the analysis of the reform the author presupposes what impact the results will have on strengthening the management and development of the organizational structure of the ROC administrative-territorial units in the south of Western Siberia.